Blockchain for peer-to-peer energy trading - Yang, Jiawei (Nanyang Technological University, 2020)
This thesis presents the study of blockchain technology used in peer-to-peer energy trading. The proposed blockchain methodologies are applied in the transactions happening between prosumers, who are equipped with PV panels. The blockchain studies are focused on how smart contracts and mining process could help and support transactions from microgrids. The protocols of the proposed blockchain are Proof-of-State and Proof-of-Work. The main goal of these studies is to explore the potential capability and how deep the blockchain technology could operate technically in the power system.